Influence of electrolyte composition on properties of the MA2-1 alloy at microarc discharge oxidizing - Boris Vladimirov; Boris Krit; Valery Lyudin; Natalya Morozova; Igor Suminov; Andrey Epelfeld (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the study is caused by the demand to develop light biomedical alloys possessing controlled corrosion speed. The main aim of the study is to research the influence of electrolyte composition at microarc discharge oxidizing of MA2-1 alloy both on the maximum duration of "faultless" processing and thickness, through porosity and corrosion-protective ability of the modified layer. The methods used in the study: Plasma-electrolytic microarc discharge oxidizing. Study of through porosity when measuring electric resistance of a two-electrode electrochemical cell; which one electrode is the test sample. Nondestructive control of the modified layer thickness with use of the vortex current VT-201 gage. Potentiodynamic polarization measurements in 3 % NaCl solution with scanning rate of 1 mV/sec. according to the three-electrode scheme with use of EP-20A device. The results: the authors have determined the dependence between the technology factors of microarc discharge oxidizing (the maximum duration of "faultless" processing and electrolyte composition) and corrosion-protective ability of the formed coverings.